Penerapan Sistem Pemidanaan Terhadap Pelaku Tindak Pidana Penyalahgunaan Narkoba (Studi Kasus di Polda Jateng) - Hera Saputra; Munsharif Abdul Chalim (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
ABSTRACT Drugs are short for Psychotropic Drugs and other dangerous Drugs. Besides Drugs, another term introduced especially by the Ministry of Health of the Republic of Indonesia is a drug that is short of Narcotics, Psychotropic and Addictive Substance. Narcotics are substances or drugs derived from plants or non-plants both synthetic and semi-synthetic that can cause decreased or altered consciousness, loss of taste, reduce to eliminate pain, and can cause dependence. Similarly, Psychotropic, Psychotropic is a substance or Law Number 5 Year 1997 About Psychotropic.Result of research: 1) Misuse of narcotics regulated in Law no. 35 Year 2009 on Narcotics. Article 127 paragraph (1) of Law no. 35 Year 2009, Every Type I Narcotics Abuser for himself shall be punished with imprisonment for a maximum of 4 (four) years; Any Type II Narcotics Abuser for himself shall be subject to a maximum imprisonment of 2 (two) years; and Any Misuse of Narcotics Group III for himself shall be punished with imprisonment for a maximum of 1 (one) year. As for what is meant by Misuse is a person who uses narcotics without right or against the law. 2) Some of the obstacles in the investigation of the crime of misuse or sale of Narcotics are as follows: 1) Lack of Budget, 2) Inadequate Facilities and Infrastructure, 3) Lack of Drug Crime Investigator Personnel, 4) Light Court Decisions, 5) Mutually Binding Each Performer, 6) Dramatic Drugs Technique. Strategy to overcome the abuse of drugs conducted by Polda Central Java through the following ways: . Preventive Efforts a) Pre-empetif, b) PreventiveKeywords: Implementation of Criminal System, Crime, Drug Abuse ABSTRAK Penelitian ini berjudul Penerapan Sistem Pemidanaan Terhadap Tindak Pidana Penyalah Gunaan Narkoba (Studi Kasus di Polda Jateng). Tujuan Penelitian ini : 1) Untuk mengetahui dan menganalisa sanksi pidana terhadap tentang pelaku penyalahgunaan narkoba di Polda Jateng. 2) Untuk mengetahui dan Menganalisa hambatan-hambatan dan solusi dalam penegakan hukum untuk mengatasi penyalahgunaan narkotika di Polda Jateng.Hasil Penelitian : 1) Penyalahgunaan narkotika diatur dalam Undang-Undang No. 35 Tahun 2009 tentang Narkotika. Pasal 127 ayat (1) Undang-Undang No. 35 Tahun 2009, Setiap Penyalah Guna Narkotika Golongan I bagi diri sendiri dipidana dengan pidana penjara paling lama 4 (empat) tahun; Setiap Penyalah Guna Narkotika Golongan II bagi diri sendiri dipidana dengan pidana penjara paling lama 2 (dua) tahun; dan Setiap Penyalah Guna Narkotika Golongan III bagi diri sendiri dipidana dengan pidana penjara paling lama 1 (satu) tahun. Adapun yang dimaksud dengan Penyalah Guna adalah orang yang menggunakan narkotika tanpa hak atau melawan hukum. 2) Beberapa hambatan dalam penyidikan tindak pidana penyalahgunaan maupun penjualan Narkotika adalah sebagai berikut : 1) Kurangnya Anggaran, 2) Sarana dan Prasarana yang Kurang Memadai, 3 )Kurangnya Personil Penyidik Tindak Pidana Narkoba, 4) Putusan Pengadilan yang Ringan, 5) Saling Terikatnya Tiap Pelaku, 6) Teknik Peredaran Narkoba yang Berubah-ubah. Strategi penanggulangan penyalahgunan narkoba yang dilakukan Polda Jateng melalui cara sebagai berikut : 1. Upaya Pencegahan a) Pre-empetif, b) PreventifKata Kunci : Penerapan Sistem Pemidanaan, Tindak Pidana, Penyalahgunaan Narkoba